(2,2′-Bipyridine-κ(2) N,N′)dichloridopalladium(II) 1,4-dioxane hemisolvate - Gutiérrez Márquez, Ricardo Alfredo (International Union of Crystallography, 2014)
The asymmetric unit of the title compound, [PdCl(2)(C(10)H(8)N(2))]·0.5C(4)H(8)O(2), consists of one Pd(II) complex molecule and a half-molecule of 1,4-dioxane, the complete molecule being generated by inversion symmetry. The Pd(II) atom has an almost square-planar coordination formed by the 2,2′-bipyridine ligand and two chloride ligands. Two intramolecular C—H⋯Cl hydrogen bonds occur. In the crystal, the Pd(II) complex and 1,4-dioxane molecules are connected by C—H⋯O hydrogen bonds, forming a layer parallel to (10-1). Within the layer, weak π–π interactions [centroid–centroid distance = 3.817 (4) Å] are observed between the pyridine rings.